2008
DOI: 10.1213/01.ane.0000287684.74505.49
|View full text |Cite
|
Sign up to set email alerts
|

Compliance and Dead Space Fraction Indicate an Optimal Level of Positive End-Expiratory Pressure After Recruitment in Anesthetized Patients

Abstract: All variables showed the positive effects of PEEP in conjunction with a recruitment maneuver. Optimal PEEP was 10 cm H2O because at this pressure level the highest compliance value in conjunction with the lowest dead space fraction indicated a maximum amount of effectively expanded alveoli. FRC and Pao2 were insensitive to alveolar over-distension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 31 publications
5
84
0
6
Order By: Relevance
“…One of the validated ways of selecting optimum PEEP is the optimum level of PEEP that has been identified as maximum dynamic compliance (Max Cdyn-PEEP). [16,17] This indicates that the RM did not cause lung injury with clinical repercussion as published in a previous work by our research group. [26] The RM was performed for a much longer period of time than conventionally established to assess the impact of the RM and the inflammatory response studied by the quantification of cytokine plasma levels.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…One of the validated ways of selecting optimum PEEP is the optimum level of PEEP that has been identified as maximum dynamic compliance (Max Cdyn-PEEP). [16,17] This indicates that the RM did not cause lung injury with clinical repercussion as published in a previous work by our research group. [26] The RM was performed for a much longer period of time than conventionally established to assess the impact of the RM and the inflammatory response studied by the quantification of cytokine plasma levels.…”
Section: Discussionsupporting
confidence: 74%
“…This method has been described in relation to the estimation of open-lung PEEP. [16,17] To detect the occurrence of baro-volutrauma, the flow-time and pressure-time curves of the respirator were analysed, and to detect the presence of pneumothorax and subcutaneous emphysema, a radiography was required when the optimum lung opening was reached. We assessed whether a prolonged RM induced an inflammatory response, the data collected from each piglet were compared to the data gathered at the beginning of the experiment (baseline: MIP 15cmH 2 O, PEEP 0cmH 2 O) and to the results obtained 60 minutes following the onset of the RM (after achieving Optimum lung opening: Max Cdyn-PEEP 2cmH 2 O) (Fig.…”
Section: Lung Recruitment Maneuversmentioning
confidence: 99%
“…3 The prognostic value of V D /V T has been linked to mortality risk in ARDS [4][5][6][7] and to other important clinical indices. V D /V T is known to correlate with the severity of lung injury, [8][9][10][11][12] can be useful as an indicator of lung recruitment versus overdistention in patients with acute lung injury (ALI) and ARDS, [13][14][15][16][17] may be helpful as a predictor of successful extubation in pediatric 18 and adult patients, 19 and may be useful in diagnosing and assessing the severity of pulmonary embolism. 20,21 SEE THE RELATED EDITORIAL ON PAGE 1258 Simplified bedside calculation of V D /V T requires a measurement of the partial pressure of mean expired CO 2 (P E CO 2 ) and use of the Enghoff modification of the Bohr equation.…”
Section: Introductionmentioning
confidence: 99%
“…FRC measurements must be evaluated in conjunction with data regarding oxygenation as well as tidal compliance [33][34][35][36]. Although the latter r elates inversely to the stiff ness of the lung and/or chest wall, the tidal compliance traditionally used at the bedside does not necessarily track lung volume, as further increments of PEEP above a specifi c level may simply cause overdistension -indicated by accompanying increases of elastance [33].…”
Section: Rationale For Monitoring Frc In the Critical Care Sett Ingmentioning
confidence: 99%
“…Although the latter r elates inversely to the stiff ness of the lung and/or chest wall, the tidal compliance traditionally used at the bedside does not necessarily track lung volume, as further increments of PEEP above a specifi c level may simply cause overdistension -indicated by accompanying increases of elastance [33]. Studies conducted in lun g injury models have investigated the relationship between FRC and tidal compliance [33][34][35]. In a porcine oleic-ac id-inj ury study, Rylander et al [37] found that FRC was a more sensitive indicator of PEEP-induced aeration than was compliance.…”
Section: Rationale For Monitoring Frc In the Critical Care Sett Ingmentioning
confidence: 99%